Reproductive Health Education: Sexually Transmitted Infections in SMPIT Ishlahul Ummah Bogor - Annisa Fitri Rahmadini; Fikria Nur Ramadani (AbdimasMu UMTAS, 2022)
It is estimated that every year there are 333 million new cases of sexually transmitted infections worldwide. The highest cases of sexually transmitted infections occurred at the age of 20-24, followed by the adolescent age group, namely 15-19 years. This risk occurs because adolescents have a dangerous period, namely where adolescents are vulnerable to various dangers, including a sense of wanting to imitate something that ends in imitating inappropriate things. After all, teenagers tend to be unable to distinguish which things are allowed or not to be done. These STIs will significantly impact the lives and health of children, youth, and adults. Therefore it is necessary to provide education on the prevention of Sexually Transmitted Infections among adolescents to increase adolescent knowledge of Sexually Transmitted Infections. At SMPIT Ishlahul Ummah Leuwiliang, Bogor Regency, there are 53 people. This community service activity is carried out using a survey method in the form of interviews with 30% of students. The intervention activities were carried out for 1 day through direct lectures and active discussions with students. Based on the pretest, it was concluded that the level of knowledge of students and students about IMS was still relatively low, and based on the posttest, the results could conclude that the level of knowledge of students and students about IMS was relatively high. By increasing students' knowledge and understanding, this intervention activity is expected to be able to apply to themselves.